Сучасні умови діяльності телекомунікаційних операторів - Політова, І.В. (Культура народов Причерноморья, 2013)
Проведен анализ основных тенденций реформирования телекоммуникационного рынка.
Сделан вывод, что к основным тенденциям можно отнести: либерализацию, внедрение института
регулирования, приватизации исторического оператора. В рамках оценки либерализации проведено
сравнение ее степени по секторам. В рамках анализа внедрения регулирования приведены данные о
наличии самостоятельных регуляторных органов. В рамках анализа приватизации исторических
операторов продемонстрировано тенденцию к ежегодному росту. Проведено аналіз основних тенденцій реформування телекомунікаційного ринку. Зроблено
висновок, що до основних тенденцій можна віднести: лібералізацію, впровадження інституту
регулювання, приватизацію історичного оператора. В рамках оцінки лібералізації проведено порівняння
її ступені за секторами. В рамках аналізу запровадження регулювання наведено дані щодо наявності
самостійних регуляторних органів. В рамках аналізу приватизації історичних операторів
продемонстровано тенденцію до їх щорічного зростання. The analysis of basic trends in reforming the telecommunication market in modern conditions was
done. It is concluded that the main trends are: the liberalization of the telecommunications market, introduction
of the regulation, privatization of “historical” operator. In the framework of the assessment of the liberalization
of the telecommunications market was compared the degree of liberalization of the telecommunications market
by sectors in the world, were defined the most liberalized segments. The analysis of the introduction of the
regulation provides data on availability of self–dependent independent regulators by region, defined their main
powers. Within the analysis of privatization historical operators demonstrated a tendency toward their annual
growth. Also during the work the structural scheme of the telecommunication market of “before” and “after”
reforms was proposed. Nowadays, according to this scheme (after the completion of the reforming the
telecommunication market) to the participants of telecommunications market belong: international
organizations, governments, independent regulatory bodies, the historic operator, other telecommunications
operators, subscribers – and all of them are interrelated.